Author Identification in Economics, ... and Beyond - Thomas Krichel; Christian Zimmermann (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2013)
Identifying authorship correctly and efficiently is a difficult problem when the literature is abundant, but poorly recorded. Homonyms are tedious to differentiate. This paper describes how the field of economics has organized itself with respect to author identification. We describe the RePEc project with a special emphasis on the RePEc Author Service. We then discuss how the concept is currently being expanded to the entire scientific body with the AuthorClaim project.
Keywords: A14; 330; author identification; author service; AuthorClaim; RePEc